The conscious city: Traffic congestion and change toward sustainability in metro Vancouver - Senft, Graham (Environnement Urbain / Urban Environment)

(untitled) (Réseau Villes Régions Monde, 2009)
AbstractUsing inductive, grounded theory research, this article explores the relationship between traffic congestion and change toward sustainability in Metro Vancouver through document analysis and nineteen elite interviews. The research finds that traffic congestion can be a powerful force for change, subject to the two distinct mental models that shape perspectives, behavior, and public debate in the region. The models break down mainly along urban and suburban boundaries, creating a major split in the region and significant variation in public discourse. The paper concludes that progress toward sustainability will depend, in part, on the mental model of the region’s dominant actors.